Tuning Electronic and Morphological Properties for High‐Performance Wavelength‐Selective Organic Near‐Infrared Cavity Photodetectors. (19th November 2021) - Vanderspikken, Jochen; Liu, Quan; Liu, Zhen; Vandermeeren, Tom; Cardeynaels, Tom; Gielen, Sam; Van Mele, Bruno; Van den Brande, Niko; Champagne, Benoît; Vandewal, Koen; Maes, Wouter
Abstract: Incorporation of compact spectroscopic near‐infrared (NIR) light detectors into various wearable and handheld devices opens up new applications, such as on‐the‐spot medical diagnostics. To extend beyond the detection window of silicon, i.e., past 1000 nm, organic semiconductors are highly attractive because of their tunable absorption. In particular, organic NIR wavelength‐selective detectors have been realized by incorporating donor:acceptor thin films, exhibiting weak intermolecular charge‐transfer (CT) absorption, into an optical microcavity architecture. In this work, the alkyl side chains of the well‐known PBTTT donor polymer are replaced by alkoxy substituents, hereby redshifting the CT absorption of the polymer:PC61 BM blend. It is shown that the unique fullerene intercalation features of the PBTTT polymer are retained when half of the side chains are altered, hereby maximizing the polymer:fullerene interfacial area and thus the CT absorption strength. This is exploited to extend the detection range of organic narrow‐band photodetectors with a full‐width‐at‐half‐maximum of 30–38 nm to wavelengths between 840 and 1340 nm, yielding detectivities in the range of 5 × 10 11 to 1.75 × 10 10 Jones, despite the low CT state energy of 0.98 eV. The broad wavelength tuning range achieved using a single polymer:fullerene blend renders this system an ideal candidate for miniature NIR spectrophotometers. Abstract : Significant extension of the direct charge‐transfer absorption to longer wavelengths of the well‐known PBTTT:PC61 BM blend through polymer side chain engineering is demonstrated. When applied into an optical cavity device, the novel intercalating blend extends its employability for near‐infrared detection by more than 300 nm.